Retrograde labeling, transduction and genetic targeting allow cellular analysis of corticospinal motor neurons: Implications in health and disease. - Jara, Javier H.; Genc, Baris; Klessner, Jodi L.; Ozdinler, Hande (Frontiers in Neuroanatomy, 2014)
Corticospinal motor neurons (CSMN) have a unique ability to receive, integrate, translate, and transmit the cerebral cortex’s input toward spinal cord targets and therefore, act as a “spokesperson” for the initiation and modulation of voluntary movements that require cortical input. CSMN degeneration has an immense impact on motor neuron circuitry and is one of the underlying causes of numerous neurodegenerative diseases, such as primary lateral sclerosis, hereditary spastic paraplegia, and amyotrophic lateral sclerosis. In addition, CSMN death results in long-term paralysis in spinal cord injury patients. Detailed cellular analyses are crucial to gain a better understanding of the pathologies underlying CSMN degeneration. However, visualizing and identifying these vulnerable neuron populations in the complex and heterogeneous environment of the cerebral cortex has proved challenging. Here, we will review recent developments and current applications of novel strategies that reveal the cellular and molecular basis of CSMN health and vulnerability. Such studies hold promise for building long-term effective treatment solutions in the near future.